Pakistan : A Hard Country - Lieven, Anatol (London Allen Lane, 2011)
Large, heavily populated, and strategically placed between Iran, Afghanistan and India, Pakistan is of vital importance to the world. This book looks at how Pakistan works, and rather than seeing it as a failed state, the author treats it as a viable and coherent state.
Include Notes, Glossary, Index and Illustrations
Keywords: Pakistan -- Social conditions -- Political culture